United States, boat docked at Anchorage harbor - Sorensen, Clarence Woodrow, 1907-1982; Harris, Eugene V., 1913-1978 (1934)
North Cape boat pulled out of water onto shore. Grayscale Sorensen Safety Negatives, Binder: North & Central America 3